The Impact of Foreign Direct Investment on the Economic Growth of South Caucasus Countries - Scholer-Iordanashvil, Lela (European Scientific Journal, ESJ, 2021)
This paper focuses on the effects of foreign direct investment inflows on the economic growth in a panel of three South Caucasus countries using data from 1996-2019 periods. In this study, we applied the following control variables; trade openness, investment, real exchange rate, and population growth. Classical linear regression model was employed in this paper. Ordinary least squares methods are used for estimation. Empirical results revealed that there is no significant effect of FDI inflows on economic growth. The results show that inward FDI stock-to-GDP ratio and real GDP growth rate are positively correlated.